Protocol for establishing an Adaptive Diseases control Expert Programme in Tanzania (ADEPT) for integrating care of communicable and non-communicable diseases using tuberculosis and diabetes as a case study. Issue 4 (28th April 2021) - Mpagama, Stellah G; Ramaiya, Kaushik; Lillebæk, Troels; Mmbaga, Blandina T; Sumari-de Boer, Marion; Ntinginya, Nyanda Elias; Alffenaar, Jan-Willem; Heysell, Scott K; Bygbjerg, Ib C; Christensen, Dirk L
Abstract : Introduction: Most sub-Saharan African countries endure a high burden of communicable infections but also face a rise of non-communicable diseases (NCDs). Interventions targeting particular epidemics are often executed within vertical programmes. We establish an Adaptive Diseases control Expert Programme in Tanzania (ADEPT) model with three domains; stepwise training approach, integration of communicable and NCDs and a learning system. The model aims to shift traditional vertical programmes to an adaptive diseases management approach through integrating communicable and NCDs using the tuberculosis (TB) and diabetes mellitus (DM) dual epidemic as a case study. We aim to describe the ADEPT protocol with underpinned implementation and operational research on TB/DM. Methods and analysis: The model implement a collaborative TB and DM services protocol as endorsed by WHO in Tanzania. Evaluation of the process and outcomes will follow the logic framework. A mixed research design with both qualitative and quantitative approaches will be used in applied research action. Anticipated implementation research outcomes include at the health facilities level for organising TB/DM services, pathways of patients with TB/DM seeking care in different health facilities, factors in service delivery that need deimplementation and the ADEPT model implementation feasibility, acceptability and fidelity. Expected operational research outcomes include additional identified patients with dual TB/DM, the prevalence of comorbidities like hypertension in patients with TB/DM and final treatment outcomes of TB/DM including treatment-related complications. Findings will inform the future policies and practices for integrating communicable and NCDs services. Ethics and dissemination: Ethical approval was granted by The National Research Health Ethical Committee (Ref-No. NIMR/HQ/R.8a/Vol.IX/2988) and the implementation endorsed by the government authorities. Findings will be proactively disseminated through multiple mechanisms including peer-reviewed journals, and engagement with various stakeholders' example in conferences and social media.